Impact of the ferroelectric layer thickness on the resistive switching characteristics of ferroelectric/dielectric structures - Silva, J. M. B. (2018)
In the present work, the effect of the ferroelectric layer thickness on the resistive switching (RS) characteristics of 0.5 Ba(Zr0.2Ti0.8)O3-0.5 (Ba0.7Ca0.3)TiO3 (BCZT)/HfO2:Al2O3 (HAO) structures deposited on Pt-Si substrates in a metal-dielectric-ferroelectric-metal conﬁguration is investigated. The polarization-electric ﬁeld hysteresis loops disclose the ferroelectric nature of the Pt/BCZT/ HAO/Au structures and reveal that the remnant polarization and the coercive ﬁeld decrease with the increase in the BCZT ferroelectric layer thickness. Furthermore, the RS behavior is observed in Pt/BCZT/HAO/Au structures and is attributed to the barrier variation at the BCZT/HAO interface caused by the ferroelectric polarization ﬂipping. Besides, it is also shown that the RS ratio and the switching ﬁeld can be tuned by the thickness of the ferroelectric layer. This work intends to be a ﬁrst step to build an alternative stack that provides an efﬁcient way to develop dielectric-ferroelectric structures for RS memory devices with low power consumption.